Modified resin material, method for producing the same, friction plate, brake assembly, and vehicle
Patent Information
- Application Number
- CN202510492634.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2026-10-23
AI Technical Summary
[0002]目前现有的酚醛树脂存在固化时生成一定量的小分子副产物、成型温度高、耐热性差等缺点,导致其在高端产品应用上受到较大局限,主要是因为在高温的情况下,酚醛树脂基类产品中的酚醛树脂会出现热分解(其中大部分酚醛树脂在350℃的情况下均会出现分解),导致酚醛树脂起不到粘结作用,出现粉体脱落等情况进而导致产品的摩擦系数下降,称之为热衰退
Smart Images

Figure CN122958668A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of friction pads, specifically relating to a modified resin material and its preparation method, friction pads, braking components, and vehicles. Background Technology
[0002] Currently available phenolic resins suffer from drawbacks such as the generation of small-molecule byproducts during curing, high molding temperatures, and poor heat resistance. These limitations significantly restrict their application in high-end products. The primary reason is that under high temperatures, the phenolic resin in phenolic resin-based products undergoes thermal decomposition (most phenolic resins decompose at 350℃), causing it to lose its binding properties, resulting in powder shedding and a decrease in the product's coefficient of friction—a phenomenon known as thermal fading. Products with significant thermal fading pose certain safety hazards during use. Therefore, improving thermal fading, i.e., enhancing the heat resistance of phenolic resins, is a crucial issue that needs to be addressed. Summary of the Invention
[0003] This application aims to at least partially address one of the technical problems in the related art. To this end, one objective of this application is to provide a modified resin material and its preparation method, as well as friction pads, braking components, and vehicles. The modified resin material of this application can effectively reduce the formation of small molecule byproducts during resin curing; simultaneously, the modified resin material of this application exhibits less chain segment breakage at high temperatures, thereby significantly improving the heat resistance of the modified resin material.
[0004] A first aspect of this application discloses a modified resin material. According to embodiments of this application, the modified resin material comprises at least one of the compounds shown in Formula I, Formula II, and Formula III;
[0005]
[0006]
[0007] Among them, R1, R2, R3, R4, R5, R6, and R7 are each independently selected from one of the groups containing a benzene ring; x1, x2, and x3 are each independently positive integers in the range of 10 to 1000; y1, y2, and y3 are each independently positive integers in the range of 10 to 1000; and z1, z2, and z3 are each independently positive integers in the range of 10 to 100000.
[0008] The modified resin material according to the above embodiments of this application includes at least one of the compounds shown in Formula I, Formula II and Formula III. The modified resin material with the above structure can effectively reduce the formation of small molecule byproducts during resin curing. At the same time, the modified resin material with the above structure is not easy to break down at high temperatures, thereby greatly improving the heat resistance of the modified resin material.
[0009] In addition, the modified resin material according to the above embodiments of this application may also have the following additional technical features:
[0010] In some embodiments of this application, the modified resin material has a three-dimensional network structure.
[0011] In some embodiments of this application, R1, R2, R3, R4, R5, R6, and R7 are each independently selected from groups containing a single benzene ring or groups containing multiple benzene rings, wherein the benzene rings include substituted and / or unsubstituted benzene rings.
[0012] In some embodiments of this application, z1>y1>x1, z2>y2>x2, z3>y3>x3.
[0013] In some embodiments of this application, the modified resin material includes at least one of the compounds shown in Formula IV, Formula V, and Formula VI;
[0014]
[0015]
[0016] x4, x5, and x6 are each independent positive integers in the range of 10 to 1000; y4, y5, y6, and y7 are each independent positive integers in the range of 10 to 1000; and z4, z5, and z6 are each independent positive integers in the range of 10 to 100000.
[0017] In some embodiments of this application, z4>y 4= y5>x4, z5>y6>x5, z6>y7>x6.
[0018] A second aspect of this application discloses a friction pad. According to an embodiment of this application, the friction pad comprises the modified resin material described in the above embodiments.
[0019] The friction pads according to the above embodiments of this application use a modified resin material with the above-described structure as a binder, which improves both its heat resistance and its adhesion at high temperatures. Friction pads using modified resin material as a binder exhibit good resistance to thermal fading and excellent friction performance at high temperatures.
[0020] In addition, the friction pad according to the above embodiments of this application may also have the following additional technical features:
[0021] In some embodiments of this application, the modified resin material in the friction pad has a mass content of 6% to 8% based on the total weight of the friction pad.
[0022] In some embodiments of this application, the friction pad further includes metal fibers, glass fibers, ceramic powder, friction-reducing fillers, and friction-increasing fillers.
[0023] In some embodiments of this application, the metal fiber in the friction pad has a mass content of 30% to 40%; and / or, the glass fiber in the friction pad has a mass content of 1% to 4%; and / or, the ceramic powder in the friction pad has a mass content of 10% to 20%; and / or, the friction-reducing filler in the friction pad has a mass content of 10% to 15%; and / or, the friction-enhancing filler in the friction pad has a mass content of 15% to 20%.
[0024] In some embodiments of this application, the metal fiber includes at least one of iron fiber and copper fiber; and / or, the ceramic powder includes at least one of alumina, copper oxide and silicon oxide; and / or, the wear-reducing filler includes at least one of graphite, copper sulfide, iron sulfide, molybdenum sulfide, antimony sulfide and potassium titanate; and / or, the wear-enhancing filler includes at least one of zircon, alumina, silicon carbide, silicon oxide, chromite and zirconium silicate.
[0025] In some embodiments of this application, the nominal coefficient of friction μ of the friction pad is... mon The range is 0.440 to 0.480.
[0026] A third aspect of this application provides a method for preparing the modified resin material described in the above embodiments. According to an embodiment of this application, the method includes:
[0027] The resin material and the phenyl ring amine curing agent are mixed and heated to react, thus obtaining the modified resin material.
[0028] According to the method for preparing modified resin materials according to the above embodiments of this application, a benzene ring amine curing agent is used to modify the resin material to form a modified resin material. The modified resin material formed by this method can effectively reduce the formation of small molecule byproducts during resin curing; at the same time, the chain segments of the modified resin material formed by this method are not easily broken at high temperatures, thereby significantly improving the heat resistance of the modified resin material.
[0029] In addition, the method according to the above embodiments of this application may also have the following additional technical features:
[0030] In some embodiments of this application, the mass ratio of the resin material to the phenyl cyclic amine curing agent is (5-10):(1-5).
[0031] In some embodiments of this application, the mass ratio of the resin material to the phenylcyclic amine curing agent is (7-9):1.
[0032] In some embodiments of this application, the resin material includes at least one of phenolic resin, furfural resin, urea-formaldehyde resin, and epoxy resin.
[0033] In some embodiments of this application, the benzene ring amine curing agent includes at least one of aniline, benzene ring-containing polyurethane, bisphenol A type benzoxazine, benzene ring-containing pyridine, and thiobenzoxazine.
[0034] In some embodiments of this application, the temperature at which the resin material and the phenyl ring amine curing agent are heated to react is 120°C to 150°C, and the time is 1 hour to 2 hours.
[0035] A fourth aspect of this application discloses a braking assembly. According to an embodiment of this application, the braking assembly comprises a modified resin material of the first aspect, a friction pad of the second aspect, or a modified resin material prepared by the method of the third aspect. The braking assembly can use the aforementioned friction pad as a brake lining, thereby providing the braking assembly with good resistance to thermal fading and good frictional performance at high temperatures.
[0036] The fifth aspect of this application discloses a vehicle. According to an embodiment of this application, the vehicle includes a modified resin material as described in the first aspect, a friction pad as described in the second aspect, a modified resin material prepared by the method of the third aspect, or a braking component as described in the fourth aspect. Therefore, the vehicle of this application maintains excellent braking performance even at high temperatures, thereby improving vehicle safety. It should be noted that the features and advantages described above for the friction pad also apply to this vehicle, and will not be repeated here.
[0037] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0038] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0039] Figure 1 This is a schematic diagram of the three-dimensional network structure of a modified resin material according to some embodiments of this application. Detailed Implementation
[0040] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0041] In this invention, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined with "first" and "second" may explicitly or implicitly include at least one of those features.
[0042] The first aspect of this application discloses a modified resin material. According to embodiments of this application, the modified resin material includes at least one of the compounds shown in Formula I, Formula II, and Formula III;
[0043]
[0044] Wherein, R1, R2, R3, R4, R5, R6, and R7 are each independently selected from one of the groups containing a benzene ring; x1, x2, and x3 are each independently positive integers in the range of 10 to 1000 (for example, x1, x2, and x3 can each independently be 10, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.); and y1, y2, and y3 are each independently positive integers in the range of 10 to 1000 (for example, y1, x2, and x3 can each independently be 10, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.). 1. y2 and y3 can each be independently 10, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc., and z1, z2, z3 can each be independently positive integers in the range of 10 to 100000 (for example, z1, z2, z3 can each be independently 10, 100, 1000, 3000, 5000, 8000, 10000, 30000, 50000, 80000, 100000, etc.).
[0045] It should be noted that the compound shown in Formula I above includes two structures, namely Formula I-1 and Formula I-2, wherein Formula I-1 contains a carbonyl group, and Formula I-2 does not contain a carbonyl group.
[0046]
[0047] The beneficial effects achievable by the modified resin material proposed in this application will be described in detail below:
[0048] The modified resin material of this application includes at least one of the compounds shown in Formula I, Formula II, and Formula III. The modified resin material with the above structure can effectively reduce the formation of small molecule byproducts during resin curing. Simultaneously, the modified resin material with the above structure is less prone to chain segment breakage at high temperatures, thereby significantly improving the heat resistance of the modified resin material. In particular, it can increase the decomposition temperature of phenolic resin from 350°C to approximately 550°C, significantly improving the heat resistance of phenolic resin.
[0049] According to some specific embodiments of this application, the modified resin material has a three-dimensional network structure. The modified resin material of this application has a three-dimensional network structure of resin-phenylene ring amine curing agent-resin, as shown in the attached figure. Figure 1 As shown. The three-dimensional network structure of the modified resin material of this application can reduce the formation of small molecule byproducts during resin curing. Specifically, the phenolic hydroxyl groups or hydroxyl groups, some unreacted intermediates or free phenols in the resin will react with the curing agent, reducing the volatilization of intermediates or free phenols, thereby reducing the formation of small molecule byproducts during resin curing. At the same time, the three-dimensional network structure is interpenetrating, forming a certain interpenetrating network, and the chain segments are not easily broken at high temperatures, thus significantly improving the heat resistance of the modified resin material. In particular, the three-dimensional network structure of this application increases the decomposition temperature of phenolic resin from 350℃ to about 550℃, significantly improving the heat resistance of phenolic resin.
[0050] This application utilizes a modified resin material with a three-dimensional network structure of resin-phenylene ring amine curing agent-resin as a binder, which improves both its heat resistance and adhesion at high temperatures. Friction pads using the modified resin material as a binder exhibit good resistance to thermal fading and excellent friction performance at high temperatures.
[0051] In the embodiments of this application, the modified resin material is formed by modifying the resin with a benzene ring amine curing agent during the curing process. This is mainly achieved by the reaction of phenolic hydroxyl groups or hydroxyl groups on the resin with the amine groups of adjacent monomers to form a three-dimensional network structure with multiple crosslinks, linked by methylene bridges (-CH2-) and / or Mannich bases (-NH-CH2-). Specifically, the compound shown in Formula III has a methylene bridge structure, the compound shown in Formula II has a Mannich base structure, and the compound shown in Formula I contains both a methylene bridge structure and a Mannich base structure. Furthermore, the specific type of resin is not particularly limited. As some specific embodiments, the resin includes at least one of phenolic resin, furfural resin, urea-formaldehyde resin, and epoxy resin, with phenolic resin being preferred due to its superior adhesive properties and high-temperature resistance. The specific types of the aforementioned benzene ring amine curing agents are not particularly limited. As some specific examples, the aforementioned benzene ring amine curing agents include at least one of aniline, benzene ring-containing polyurethane, bisphenol A type benzoxazine, benzene ring-containing pyridine, and thiobenzoxazine. Bisphenol A type benzoxazine is preferred. Bisphenol A type benzoxazine has two benzene rings, which has better heat resistance. Polybenzene ring compounds have better heat resistance than monobenzene ring compounds, and the benzene rings are not easily broken.
[0052] According to some specific embodiments of this application, R1, R2, R3, R4, R5, R6, and R7 are each independently selected from groups containing a single benzene ring or groups containing multiple benzene rings, wherein the benzene ring includes substituted and / or unsubstituted benzene rings. A single benzene ring refers to a simple benzene ring in which the hydrogen atoms on the single benzene ring are unsubstituted or at least one hydrogen atom is substituted by a functional group. Multiple benzene rings refer to a structure in which two or more benzene rings are connected together by sharing a carbon atom or by other atoms (such as oxygen, nitrogen, etc.), and the hydrogen atoms on the multiple benzene rings are unsubstituted or at least one hydrogen atom is substituted by a functional group. These functional groups can be hydroxyl (-OH), carboxyl (-COOH), amino (-NH2), ether (-O-), halogen (-Cl, -Br, etc.), etc. As some specific examples, R1, R2, R3, R4, R5, R6, and R7 are each independently selected from... or wait.
[0053] According to some specific embodiments of this application, z1>y1>x1, z2>y2>x2, z3>y3>x3, that is, in the three-dimensional network structure of the modified resin material, the number of repeating units of the resin groups is greater than the number of connecting groups, and the number of connecting groups is greater than the number of repeating units of the benzene ring amine curing agent groups, as shown in the appendix. Figure 1 As shown. The reason is that the resin may contain unreacted phenol or intermediates, and one curing agent molecule can be linked to multiple resin molecules.
[0054] Many phenolic resins readily decompose at temperatures of 350°C and higher, producing products such as carbon dioxide, toluene, and phenol, rendering them unusable at high temperatures. Especially in friction materials, the decomposition of phenolic resin at high temperatures leads to the continuous generation of gases such as carbon dioxide within the friction pads. This can cause bulging or cracking of the friction pads, and in severe cases, prevent the vehicle from stopping, posing a safety hazard. Therefore, it is necessary to improve the heat resistance of phenolic resins. The better the heat resistance of phenolic resin-based friction pads, the better their friction performance at high temperatures, increasing safety. According to further specific embodiments of this application, the modified phenolic resin material includes at least one of the compounds shown in Formula IV, Formula V, and Formula VI.
[0055]
[0056] x4, x5, and x6 are each independently a positive integer in the range of 10 to 1000 (for example, x4, x5, and x6 can each independently be 10, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.), and y4, y5, y6, and y7 are each independently a positive integer in the range of 10 to 1000 (for example, y4, y5, y6, and y7 can each independently be 10, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.). 00, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.), z4, z5, z6 are each independently positive integers in the range of 10 to 100000 (for example, z4, z5, z6 can each independently be 10, 100, 1000, 3000, 5000, 8000, 10000, 30000, 50000, 80000, 100000, etc.).
[0057] According to embodiments of this application, the modified phenolic resin material includes at least one of the compounds shown in Formula IV, Formula V, and Formula VI. It is evident that the modified phenolic resin material possesses a three-dimensional network structure of phenolic resin-bisphenol A type benzoxazine curing agent-phenolic resin, as shown in the attached figure. Figure 1As shown. The three-dimensional network structure of the modified phenolic resin material in this application can reduce the formation of small molecule byproducts during the curing of phenolic resin. Specifically, the phenolic hydroxyl groups, some unreacted intermediates, or free phenols in the phenolic resin react with the curing agent, reducing the volatilization of intermediates or free phenols, thereby reducing the formation of small molecule byproducts during the curing of phenolic resin. At the same time, the three-dimensional network structure is interpenetrating, forming a certain interpenetrating network, making the chain segments less prone to breakage at high temperatures, thus significantly improving the heat resistance of the modified phenolic resin material. Specifically, the three-dimensional network structure of this application increases the decomposition temperature of phenolic resin from 350℃ to about 550℃, significantly improving the heat resistance of phenolic resin. In addition, this application uses a modified phenolic resin material with a three-dimensional network structure of phenolic resin-bisphenol A type benzoxazine curing agent-phenolic resin as a binder, which also improves its adhesion at high temperatures. Therefore, friction pads using modified phenolic resin material as a binder have good resistance to thermal fading and good friction performance at high temperatures.
[0058] In the embodiments of this application, the modified phenolic resin material is formed by modifying the phenolic resin with a bisphenol A type benzoxazine curing agent during the curing process. This is mainly achieved through the reaction of the phenolic hydroxyl groups on the phenolic resin with the amino groups of adjacent monomers, forming a three-dimensional network structure with multiple crosslinks connected by methylene bridges (-CH2-) and / or Mannich bases (-NH-CH2-). Specifically, the formation of the methylene bridge structure occurs as follows: under certain conditions, the NO heterocycle of the benzoxazine undergoes a ring-opening reaction, forming active hydroxyl and amino groups. The phenolic hydroxyl groups and the active hydrogens (-CH2OH) at the ortho / para positions in the phenolic resin react with the active hydroxyl or amino groups formed on the benzoxazine to form methylene bridges (-CH2-) or ether bonds (-O-). The formation of the Mannich base structure occurs as follows: under certain conditions, the NO heterocycle of the benzoxazine undergoes a ring-opening reaction, forming active hydroxyl and amino groups. Under acidic conditions, the hydroxymethyl group of the phenolic resin undergoes deprotonation, forming oxonium ions (-CH2OH2). + Then, the active amino group on the benzoxazine reacts with the deprotonated hydroxymethyl carbonyl carbon, followed by dehydration to form the Mannich base structure (-NH-CH2-). Among them, the compound shown in formula VI has a methylene bridge structure, the compound shown in formula V has a Mannich base structure, and the compound shown in formula IV contains both a methylene bridge structure and a Mannich base structure.
[0059] According to some specific embodiments of this application, z4>y 4=y5>x4, z5>y6>x5, z6>y7>x6. That is, in the three-dimensional network structure of the modified phenolic resin material, the number of repeating units of the phenolic resin groups is greater than the number of linking groups, and the number of linking groups is greater than the number of repeating units of the benzene ring amine curing agent groups. This is because phenolic resins may contain unreacted phenol or intermediates, and one benzene ring amine curing agent molecule can be linked to multiple phenolic resin molecules. Furthermore, in formula IV, the number of methylene bridges is equal to the number of Mannich bases, i.e., y 4= y5, but the methylene bridge and Mannich base have different orientations in the three-dimensional network structure.
[0060] A second aspect of this application discloses a friction pad. According to an embodiment of this application, the friction pad comprises the modified resin material described in the above embodiments.
[0061] The friction pads according to the above embodiments of this application use a modified resin material having the above structure as a binder, which improves both its heat resistance and its adhesion at high temperatures. Friction pads using modified resin materials as binders exhibit good resistance to thermal fading and good frictional performance at high temperatures.
[0062] Furthermore, the aforementioned friction pad uses a modified resin material with a three-dimensional network structure of resin-phenylene ring amine curing agent-resin as a binder, which improves its heat resistance and adhesion at high temperatures. The friction pad using the modified resin material as a binder exhibits good resistance to thermal fading and excellent friction performance at high temperatures.
[0063] According to some specific embodiments of this application, the modified resin material in the friction pad is 6% to 8% by weight, for example, 6%, 6.5%, 7%, 7.5%, 8%, etc. By limiting the mass content of the modified resin material in the friction pad to the above range, the bonding performance of the modified resin material as a binder in the friction pad can be further ensured, avoiding situations such as powder shedding that would lead to a decrease in the friction coefficient of the brake pad, thereby further ensuring the friction performance of the friction pad.
[0064] According to further specific embodiments of this application, the aforementioned friction pad further includes metal fibers, glass fibers, ceramic powder, friction-reducing fillers, and friction-increasing fillers. Metal fibers possess high strength and toughness, effectively improving the overall mechanical properties of the friction pad and enhancing its tensile, compressive, and impact resistance. Simultaneously, metal fibers have good thermal conductivity, quickly dispersing heat generated during braking and preventing localized overheating, thereby improving the thermal stability of the friction pad. Glass fibers possess high strength and high modulus, significantly improving the mechanical strength and rigidity of the friction pad. Furthermore, glass fibers have good heat resistance, remaining stable at high temperatures, contributing to improved heat resistance. Additionally, glass fibers reduce thermal expansion of the friction pad at high temperatures, maintaining its dimensional stability. Ceramic powder has high hardness, improving the wear resistance of the friction pad and reducing wear. Simultaneously, ceramic powder has good heat resistance, remaining stable at high temperatures, contributing to improved resistance to thermal degradation. Furthermore, ceramic powder can adjust the friction coefficient of the friction pad, ensuring stable friction performance under different operating conditions. Anti-friction fillers, such as graphite and molybdenum disulfide, can form a lubricating film on the surface of the friction pads, reducing the coefficient of friction and decreasing energy loss during braking. By reducing the coefficient of friction, anti-friction fillers can effectively reduce wear between the friction pads and the brake disc, extending their service life. Anti-friction fillers, such as aluminum oxide, can increase the coefficient of friction of the friction pads, ensuring sufficient braking force during braking and maintaining a stable coefficient of friction under different operating conditions.
[0065] According to some specific embodiments of this application, the mass content of metal fiber in the friction plate is 30% to 40%, for example, it can be 30%, 32%, 34%, 36%, 38%, 40%, etc. By limiting the mass content of metal fiber in the friction plate to the above range, it is possible to further ensure the improvement of the overall mechanical properties of the friction plate, enhance its tensile, compressive and impact resistance, and further ensure the improvement of the thermal stability of the friction plate.
[0066] According to some specific embodiments of this application, the mass content of glass fiber in the friction pad is 1% to 4%, for example, it can be 1%, 2%, 3%, 4%, etc. By limiting the mass content of glass fiber in the friction pad to the above range, it is possible to further ensure that the mechanical strength and rigidity, heat resistance and dimensional stability of the friction pad are improved.
[0067] According to some specific embodiments of this application, the mass content of ceramic powder in the friction plate is 10% to 20%, for example, it can be 10%, 12%, 14%, 16%, 18%, 20%, etc. By limiting the mass content of ceramic powder in the friction plate to the above range, it is possible to further ensure that the wear resistance and heat fading resistance of the friction plate are improved, and at the same time, it is possible to further ensure that it maintains stable friction performance under different working conditions.
[0068] According to some specific embodiments of this application, the mass content of the anti-friction filler in the friction plate is 10% to 15%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, etc. By limiting the mass content of the anti-friction filler in the friction plate to the above range, it can be further ensured that a lubricating film is formed on the surface of the friction plate, reducing the coefficient of friction, reducing energy loss during braking, and extending service life.
[0069] According to some specific embodiments of this application, the mass content of the friction-enhancing filler in the friction plate is 15% to 20%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, etc. By limiting the mass content of the friction-enhancing filler in the friction plate to the above range, it is possible to further ensure that the friction coefficient of the friction plate is improved and that there is sufficient braking force during braking.
[0070] In the embodiments of this application, the specific types of metal fibers are not particularly limited. As some specific embodiments, the metal fibers include at least one of iron fibers and copper fibers. The specific types of ceramic powder are also not particularly limited. As some specific embodiments, the ceramic powder includes at least one of alumina, copper oxide, and silicon oxide. The specific types of wear-reducing fillers are also not particularly limited. As some specific embodiments, the wear-reducing fillers include at least one of graphite, copper sulfide, iron sulfide, molybdenum sulfide, antimony sulfide, and potassium titanate. The specific types of wear-increasing fillers are also not particularly limited. As some specific embodiments, the wear-increasing fillers include at least one of zircon, alumina, silicon carbide, silicon oxide, chromite, and zirconium silicate.
[0071] According to some specific embodiments of this application, the nominal coefficient of friction μ of the above-mentioned friction sheet mon The coefficient of friction ranges from 0.440 to 0.480, for example, it can be 0.440, 0.450, 0.460, 0.470, 0.480, etc., indicating that the above-mentioned friction pads have excellent overall friction performance. The nominal coefficient of friction is the ratio of the frictional force between the surfaces of two objects to the normal force, and it is a physical quantity that reflects the frictional characteristics between the surfaces of objects.
[0072] In the embodiments of this application, the friction pad can be used as a brake pad.
[0073] A third aspect of this application provides a method for preparing the modified resin material of the above embodiments. According to an embodiment of this application, the method includes: S100: mixing the resin material and a phenyl ring amine curing agent, heating and reacting to obtain the modified resin material.
[0074] In this step, the resin material and the phenylcyclic amine curing agent are added to a stirrer, mixed and stirred, and heated to react. The phenolic hydroxyl groups on the resin react with the amine groups of adjacent monomers on the phenylcyclic amine curing agent to form a three-dimensional network structure with multiple crosslinks, connected by methylene bridges (-CH2-) and / or Mannich bases (-NH-CH2-), to obtain the modified resin material, as shown in Formulas I, II, and III. Specifically, the compound shown in Formula III has a methylene bridge structure, the compound shown in Formula II has a Mannich base structure, and the compound shown in Formula I contains both a methylene bridge structure and a Mannich base structure.
[0075] In the embodiments of this application, the specific type of resin is not particularly limited. As some specific embodiments, the resin includes at least one of phenolic resin, furfural resin, urea-formaldehyde resin, and epoxy resin, with phenolic resin being preferred, as it has superior adhesive properties and high-temperature resistance. The specific type of the benzene ring amine curing agent is also not particularly limited. As some specific embodiments, the benzene ring amine curing agent includes at least one of aniline, benzene ring-containing polyurethane, bisphenol A type benzoxazine, benzene ring-containing pyridine, and thiobenzoxazine, with bisphenol A type benzoxazine being preferred. Bisphenol A type benzoxazine has two benzene rings, resulting in better heat resistance. Polyphenyl ring compounds have better heat resistance than monophenyl ring compounds, and the benzene rings are less prone to breakage. As a specific example, when phenolic resin reacts with bisphenol A type benzoxazine, modified phenolic resin materials with compounds as shown in Formulas IV, V, and VI can be generated.
[0076] According to some specific embodiments of this application, the mass ratio of resin material to phenylcyclic amine curing agent is (5-10):(1-5), for example, it can be 5:5, 5:2.5, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc. By limiting the mass ratio of resin material to phenylcyclic amine curing agent within the above range, it can be further ensured that the reaction between resin material and phenylcyclic amine curing agent can form a modified resin material with a three-dimensional network structure of resin-phenylcyclic amine curing agent-resin. Preferably, the mass ratio of resin material to phenylcyclic amine curing agent is (7-9):1.
[0077] According to further specific embodiments of this application, the temperature for heating the resin material and the phenylcyclic amine curing agent is 120°C to 150°C (e.g., 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, etc.), and the time is 1 hour to 2 hours (e.g., 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, etc.). By limiting the temperature and time of the heating reaction between the resin material and the phenylcyclic amine curing agent to the above range, it can be further ensured that the resin material and the phenylcyclic amine curing agent can fully react to form a modified resin material with a three-dimensional network structure of resin-phenylcyclic amine curing agent-resin. Preferably, the temperature is 125°C to 135°C.
[0078] According to the method for preparing modified resin materials according to the above embodiments of this application, a phenylcyclic amine curing agent is used to modify the resin material to form a modified resin material, which has a three-dimensional network structure of resin-phenylcyclic amine curing agent-resin. The three-dimensional network structure of the modified resin material formed by this method can reduce the formation of small molecule byproducts during resin curing; simultaneously, the three-dimensional network structure is interpenetrating, forming a certain interpenetrating network, making the chain segments less prone to breakage at high temperatures, thereby significantly improving the heat resistance of the modified resin material. In particular, the three-dimensional network structure of this application increases the decomposition temperature of phenolic resin from 350°C to approximately 550°C, significantly improving the heat resistance of phenolic resin.
[0079] In addition, in the embodiments of this application, the method for preparing the above-mentioned friction pad includes the following steps:
[0080] S200: A mixture is prepared by mixing modified resin material, metal fiber, glass fiber, ceramic powder, wear-reducing filler and wear-increasing filler.
[0081] In this step, modified resin materials, metal fibers, glass fibers, ceramic powder, anti-friction fillers, and anti-friction fillers can be put into the plow and harrow mixer and mixed evenly to obtain a mixture.
[0082] S300: Hot pressing is performed on the mixture to obtain a hot-pressed product;
[0083] In this step, the mixture is hot-pressed to tightly bind the various raw material components together, resulting in a hot-pressed product. The hot-pressing process can press the mixture into the desired shape, such as round, square, or other complex shapes, to meet the dimensional requirements of the friction pads.
[0084] According to some specific embodiments of this application, the temperature for hot pressing the mixture is 120℃~150℃ (e.g., 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, etc.), the pressure is 30MPa~50MPa (e.g., 30MPa, 35MPa, 40MPa, 45MPa, 50MPa, etc.), and the holding time is 10min~15min (e.g., 10min, 11min, 12min, 13min, 14min, 15min, etc.).
[0085] S400: Post-curing treatment is applied to hot-pressed products to obtain friction pads.
[0086] In this step, the hot-pressed product undergoes post-curing treatment to obtain the friction pad. During the hot-pressing process, certain internal stresses may be generated within the product. Post-curing treatment releases these internal stresses by initially maintaining the product at a lower temperature for a period of time, thus preventing deformation or cracking during subsequent use. A more complete curing reaction is then completed at a higher temperature, forming a more stable three-dimensional network structure, which helps improve the product's heat resistance and mechanical properties. Simultaneously, the post-curing process further removes residual low-molecular-weight substances from the product, thereby reducing their negative impact on product performance.
[0087] According to some specific embodiments of this application, the post-curing treatment can be carried out by programmed temperature rise: First, the hot-pressed product is kept at 120℃~150℃ (e.g., 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, etc.) for 4h~6h (e.g., 4h, 4.5h, 5h, 5.5h, 6h, etc.) to release the internal stress of the product, thereby preventing deformation or cracking during subsequent use. Then, the temperature is raised to 180℃~200℃ (e.g., 180℃, 185℃, 190℃, 195℃, 200℃, etc.) and kept at 180℃~200℃ for 6h~8h (e.g., 6h, 6.5h, 7h, 7.5h, 8h, etc.) to complete a more complete curing reaction, forming a more stable three-dimensional network structure, while further removing residual low-molecular-weight substances inside the product, resulting in a friction pad.
[0088] The method for preparing friction pads according to the above embodiments of this application uses a modified resin material with a three-dimensional network structure of resin-phenylene ring amine curing agent-resin as a binder to prepare the friction pads. This improves both the heat resistance and adhesion of the friction pads at high temperatures. Friction pads using modified resin materials as binders exhibit good resistance to thermal fading and excellent friction performance at high temperatures.
[0089] A fourth aspect of this application discloses a braking assembly. According to an embodiment of this application, the braking assembly comprises a modified resin material of the first aspect, a friction pad of the second aspect, or a modified resin material prepared by the method of the third aspect. The braking assembly can use the aforementioned friction pad as a brake lining, thereby providing the braking assembly with good resistance to thermal fading and good frictional performance at high temperatures.
[0090] Specifically, in addition to brake pads, the braking assembly may also include: brake pedal, master cylinder, brake fluid, brake disc / disc, brake caliper, brake lines and hoses, brake caliper / wheel cylinder, brake pad wear sensor, brake fluid level sensor, electronic stability control system (ESC), handbrake, etc. These components work together to ensure the normal operation of the braking system and the safety of vehicle driving.
[0091] The fifth aspect of this application discloses a vehicle. According to an embodiment of this application, the vehicle includes a modified resin material as described in the first aspect, a friction pad as described in the second aspect, a modified resin material prepared by the method of the third aspect, or a braking component as described in the fourth aspect. Therefore, the vehicle of this application maintains excellent braking performance even at high temperatures, thereby improving vehicle safety. It should be noted that the features and advantages described above for the friction pad also apply to this vehicle, and will not be repeated here.
[0092] It is understood that there are no particular restrictions on the specific types of vehicles mentioned above; any vehicle that requires friction pads is acceptable. For example, the vehicles mentioned above can be automobiles (such as cars, RVs, trucks, transport vehicles, lorries, buses, etc.) and trains (such as regular trains, high-speed trains, etc.).
[0093] It is understood that, in addition to the friction pads mentioned above, the vehicle has the necessary structures and components in conventional technology. Taking a car as an example, it may include the chassis, body, tires, engine, central control, seat interior, and other necessary structures and components of a conventional car, which will not be described in detail in this application.
[0094] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.
[0095] Example 1
[0096] This embodiment provides a friction pad, the preparation method of which includes the following steps:
[0097] S1: Preparation of modified phenolic resin: Phenolic resin and bisphenol A type benzoxazine are fed into a stirrer at a mass ratio of 9:1 and stirred continuously at 120℃ for 2 hours, so that the phenolic hydroxyl groups on the phenolic resin react with the amino groups of the adjacent monomers on the curing agent to form a modified phenolic resin with a three-dimensional network structure of phenolic resin-phenyl ring amine curing agent-phenolic resin.
[0098] S2: According to the quality formula design, 8% modified phenolic resin, 35% metal fiber (including 25% steel fiber and 10% copper fiber), 2% glass fiber, 20% ceramic powder (including 2% magnesium oxide, 4% silicon powder, 2% calcium hydroxide, 2% calcium carbonate, and 10% barium sulfate), 15% grinding-reducing filler (including 1% potassium titanate, 4% molybdenum sulfide, 2% iron sulfide, and 8% graphite), and 20% grinding-enhancing filler (including 4% zircon, 8% alumina, 2% silicon oxide, and 6% chromite) are added to the plow and rake mixer and mixed evenly to obtain the mixture.
[0099] S3: The mixture obtained in step S2 is hot-pressed to obtain a hot-pressed product. The molding temperature is 145℃, the molding pressure is 43MPa, and the holding time is 10min.
[0100] S4: The hot-pressed product obtained in step S3 is subjected to curing treatment, and then kept at 140℃ for 6 hours, and then heated to 200℃ for 8 hours to finally obtain a high heat-resistant friction brake pad (i.e., friction pad).
[0101] Example 2
[0102] This embodiment is basically the same as Embodiment 1, except for step S1:
[0103] The phenolic resin in Example 1 was replaced with furfural resin, and the bisphenol A type benzoxazine in Example 1 was replaced with aniline.
[0104] Example 3
[0105] This embodiment is basically the same as Embodiment 1, except for step S1:
[0106] The phenolic resin in Example 1 was replaced with urea-formaldehyde resin, and the bisphenol A type benzoxazine in Example 1 was replaced with thiobenzoxazine.
[0107] Example 4
[0108] This embodiment is basically the same as Embodiment 1, except for step S1:
[0109] The phenolic resin in Example 1 was replaced with epoxy resin, and the bisphenol A type benzoxazine in Example 1 was replaced with polyurethane containing benzene rings.
[0110] Example 5
[0111] This embodiment is basically the same as Embodiment 1, except for step S1:
[0112] Phenolic resin and bisphenol A type benzoxazine were fed in a mass ratio of 5:5.
[0113] Example 6
[0114] This embodiment is basically the same as Embodiment 1, except for step S1:
[0115] Phenolic resin and bisphenol A type benzoxazine were fed in a mass ratio of 5:1.
[0116] Example 7
[0117] This embodiment is basically the same as Embodiment 1, except for step S1:
[0118] Phenolic resin and bisphenol A type benzoxazine were fed in a mass ratio of 7:1.
[0119] Example 8
[0120] This embodiment is basically the same as Embodiment 1, except for step S1:
[0121] Phenolic resin and bisphenol A type benzoxazine were fed in a mass ratio of 10:1.
[0122] Example 9
[0123] This embodiment is basically the same as Embodiment 1, except for step S1:
[0124] Phenolic resin and bisphenol A type benzoxazine were fed in a mass ratio of 11:1.
[0125] Example 10
[0126] This embodiment is basically the same as Embodiment 1, except for step S1:
[0127] Phenolic resin and bisphenol A type benzoxazine were fed in a mass ratio of 4:6.
[0128] Example 11
[0129] This embodiment is basically the same as Embodiment 1, except for step S1:
[0130] The reaction was carried out with continuous stirring at 125°C for 2 hours.
[0131] Example 12
[0132] This embodiment is basically the same as Embodiment 1, except for step S1:
[0133] The reaction was carried out at 135°C with continuous stirring for 2 hours.
[0134] Example 13
[0135] This embodiment is basically the same as Embodiment 1, except for step S1:
[0136] The reaction was stirred continuously at 150°C for 1 hour.
[0137] Comparative Example 1
[0138] This comparative example is basically the same as Example 1, except that:
[0139] Without modifying the phenolic resin, according to the quality formula design, 8% phenolic resin, 35% metal fiber, 2% glass fiber, 20% ceramic powder, 15% anti-friction filler, and 20% grinding-enhancing filler were added into a plow-harrow mixer and mixed evenly to obtain a mixture. All other steps were the same as in Example 1.
[0140] Performance testing
[0141] The brake pads (i.e., friction pads) prepared in Examples 1-13 and Comparative Example 1 were subjected to the AK test (an achievable test method for evaluating brake pad performance, which mainly uses an inertial dynamometer to simulate the actual braking process to evaluate the friction performance and braking effect of the brake pads under different operating conditions) using a LINK3900. The test standard was SAE J2522, with the highest thermal fade temperature reaching over 600℃. The AK test results are shown in Table 1. The nominal coefficient of friction μ... mon The values were obtained by testing and calculation according to SAE J2522 standard. The specific process of heat fade 1 is as follows: braking begins at 100℃, braking from 100km / h to 1km / h, and then repeating this process 15 times. The starting temperatures for each of the 15 braking cycles are, in sequence: 100℃, 215℃, 283℃, 330℃, 367℃, 398℃, 423℃, 446℃, 465℃, 483℃, 498℃, 513℃, 526℃, 539℃, and 550℃. The average friction coefficient μ under heat fade 1 condition is... mon = Average friction coefficient of 15 braking cycles under thermal fade 1.
[0142] Then, the same procedure was followed for heat fade 2. Specifically, braking was initiated at 100°C, with the braking speed decreasing from 100 km / h to 1 km / h, and this process was repeated 15 times. The starting temperatures for each of the 15 braking operations were 100°C, 215°C, 283°C, 330°C, 367°C, 398°C, 423°C, 446°C, 465°C, 483°C, 498°C, 513°C, 526°C, 539°C, and 550°C, respectively. The average friction coefficient μ under the heat fade 2 condition was... mon = Average friction coefficient of 15 braking cycles under thermal fade 2.
[0143] Table 1
[0144]
[0145]
[0146] As can be seen from Table 1, compared with Comparative Example 1, the nominal coefficient of friction μ of the brake pads (i.e., friction pads) in Examples 1-13 is... mon The minimum coefficient of friction μ that occurs under all operating conditions min The average friction coefficient μ under thermal decay condition 1 mon Minimum coefficient of friction μ under thermal decay condition 1 min The average friction coefficient μ under thermal decay condition 2 mon Minimum coefficient of friction μ under thermal decay condition 2 min Both were significantly improved, indicating that friction pads using modified resin materials with a three-dimensional network structure of resin-phenyl cyclic amine curing agent-resin as binders have good resistance to thermal degradation and friction performance at high temperatures.
[0147] As can be seen from Table 1, compared with Examples 9 and 10, the nominal coefficient of friction μ of the brake pads (i.e., friction pads) in Examples 1, 5 to 8 is higher. mon The minimum coefficient of friction μ that occurs under all operating conditions min The average friction coefficient μ under thermal decay condition 1 mon Minimum coefficient of friction μ under thermal decay condition 1 min The average friction coefficient μ under thermal decay condition 2 mon Minimum coefficient of friction μ under thermal decay condition 2 min Both are quite excellent. It can be seen that when the mass ratio of resin material and phenyl ring amine curing agent is limited to the range of (5~10):(1~5), the friction pad prepared by the modified resin material has excellent heat fading resistance and friction performance at high temperature.
[0148] As can be seen from Table 1, compared with Examples 5-6 and Example 8, the nominal coefficient of friction μ of the brake pads (i.e., friction pads) in Examples 1 and 7 is... mon The minimum coefficient of friction μ that occurs under all operating conditions min The average friction coefficient μ under thermal decay condition 1 mon Minimum coefficient of friction μ under thermal decay condition 1 min The average friction coefficient μ under thermal decay condition 2 mon Minimum coefficient of friction μ under thermal decay condition 2 min It is even more superior. It can be seen that by limiting the mass ratio of resin material and benzene ring amine curing agent to the range of (7~9):1, the friction pad prepared by the modified resin material has better resistance to thermal fading and friction performance at high temperature.
[0149] As can be seen from Table 1, compared with Examples 1 and 13, the nominal coefficient of friction μ of the brake pads (i.e., friction pads) in Examples 11 and 12 is... mon The minimum coefficient of friction μ that occurs under all operating conditions min The average friction coefficient μ under thermal decay condition 1 mon Minimum coefficient of friction μ under thermal decay condition 1 min The average friction coefficient μ under thermal decay condition 2 mon Minimum coefficient of friction μ under thermal decay condition 2 min Both are quite excellent. It can be seen that the friction pads prepared by heating the resin material and the benzene ring amine curing agent within the range of 125℃~135℃ have excellent heat fading resistance and friction performance at high temperatures.
[0150] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0151] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A modified resin material, characterized in that, The modified resin material includes at least one of the compounds shown in Formula I, Formula II, and Formula III; Among them, R1, R2, R3, R4, R5, R6, and R7 are each independently selected from one of the groups containing a benzene ring; x1, x2, and x3 are each independently positive integers in the range of 10 to 1000; y1, y2, and y3 are each independently positive integers in the range of 10 to 1000; and z1, z2, and z3 are each independently positive integers in the range of 10 to 100000.
2. The modified resin material according to claim 1, characterized in that, The modified resin material has a three-dimensional network structure.
3. The modified resin material according to claim 1, characterized in that, R1, R2, R3, R4, R5, R6, and R7 are each independently selected from groups containing a single benzene ring and groups containing multiple benzene rings, wherein the benzene rings include substituted and / or unsubstituted benzene rings.
4. The modified resin material according to claim 1, characterized in that, z1>y1>x1, z2>y2>x2, z3>y3>x3.
5. The modified resin material according to claim 1, characterized in that, The modified resin material includes at least one of the compounds shown in Formula IV, Formula V, and Formula VI; x4, x5, and x6 are each independent positive integers in the range of 10 to 1000; y4, y5, y6, and y7 are each independent positive integers in the range of 10 to 1000; and z4, z5, and z6 are each independent positive integers in the range of 10 to 100000.
6. The modified resin material according to claim 5, characterized in that, z4>y 4= y5>x4,z5>y6>x5,z6>y7>x6。 7. A friction plate, characterized in that, The friction pad comprises the modified resin material according to any one of claims 1 to 6.
8. The friction plate according to claim 7, characterized in that, The modified resin material comprises 6% to 8% of the total weight of the friction pad.
9. The friction plate according to claim 7 or 8, characterized in that, The friction pad also includes metal fibers, glass fibers, ceramic powder, friction-reducing fillers, and friction-enhancing fillers.
10. The friction plate according to claim 9, characterized in that, The metal fiber content in the friction plate is 30% to 40% by mass; And / or, the glass fiber content in the friction pad is 1% to 4% by mass; And / or, the ceramic powder in the friction plate has a mass content of 10% to 20%; And / or, the friction-reducing filler has a mass content of 10% to 15% in the friction plate; And / or, the friction-enhancing filler content in the friction plate is 15% to 20% by mass.
11. The friction plate according to claim 9, characterized in that, The metal fiber includes at least one of iron fiber and copper fiber; And / or, the ceramic powder includes at least one of alumina, copper oxide, and silicon oxide; And / or, the wear-reducing filler includes at least one of graphite, copper sulfide, iron sulfide, molybdenum sulfide, antimony sulfide, and potassium titanate; And / or, the grinding-enhancing filler includes at least one of zircon, alumina, silicon carbide, silicon oxide, chromite, and zirconium silicate.
12. The friction plate according to claim 7 or 8, characterized in that, The nominal coefficient of friction μ of the friction plate mon The range is 0.440 to 0.
480.
13. A method for preparing the modified resin material according to any one of claims 1 to 6, characterized in that, include: The resin material and the phenyl ring amine curing agent are mixed and heated to react, thus obtaining the modified resin material.
14. The method according to claim 13, characterized in that, The mass ratio of the resin material to the phenyl cyclic amine curing agent is (5-10):(1-5).
15. The method according to claim 14, characterized in that, The mass ratio of the resin material to the phenyl cyclic amine curing agent is (7-9):
1.
16. The method according to any one of claims 13 to 15, characterized in that, The resin material includes at least one of phenolic resin, furfural resin, urea-formaldehyde resin, and epoxy resin.
17. The method according to any one of claims 13 to 15, characterized in that, The benzene ring amine curing agent includes at least one of aniline, benzene ring-containing polyurethane, bisphenol A type benzoxazine, benzene ring-containing pyridine, and thiobenzoxazine.
18. The method according to any one of claims 13 to 15, characterized in that, The temperature at which the resin material and the phenyl ring amine curing agent are heated to react is 120℃~150℃, and the time is 1h~2h.
19. A braking assembly, characterized in that, It includes the modified resin material according to any one of claims 1 to 6, the friction pad according to any one of claims 7 to 12, or the modified resin material prepared by the method according to any one of claims 13 to 18.
20. A vehicle, characterized in that, It includes the modified resin material according to any one of claims 1 to 6, the friction pad according to any one of claims 7 to 12, the modified resin material prepared by the method according to any one of claims 13 to 18, or the braking assembly according to claim 19.